Gas-phase brown carbon: Absorbance and chromophore types. (1st November 2021) - Chen, Qingcai; Chen, Qian; Hua, Xiaoyu; Guan, Dongjie; Chang, Tian
Abstract: Brown carbon (BrC) is recognized as an important contributor of global warming because it can effectively absorb solar radiation in the atmosphere. Up to now, most studies mainly focused on the properties of particle-phase brown carbon (BrC-PP). The optical characteristics and environmental impacts of gas-phase brown carbon (BrC-GP) are rarely investigated. To address this knowledge gap, the BrC-PP and BrC-GP were collected simultaneously from the ambient air in an urban area for half a month in summer of 2019. The samples were extracted by methanol and were analyzed both using the UV–visible spectroscopy and the excitation-emission matrix (EEM) fluorescence spectroscopy for their optical properties and chemical compositions. The results showed that the light absorption of BrC-GP was comparable with that of BrC-PP. The BrC-GP can contribute 40% of the total light absorption by methanol-extracted BrC at the short wavelength of 400 nm. However, no significant correlation was found between BrC-GP and BrC-PP in terms of the light-absorption. It was surprising that the BrC-GP accounted for 80% of the total fluorescence volume. EEM-PARAFAC analysis showed that the BrC-PP was mainly composed of humic-like substances, while the BrC-GP was rich in phenol- and protein-like substances. Further extensive studies on the content, reactivity and seasonal trends of BrC-GP are required to clarify their environmental impacts. Graphical abstract: Image 1 Highlights: The optical properties both of particle- and gas-phase BrC was studied. The light absorption of gas-phase BrC may not negligible. The gas-phase BrC was rich in phenol- and protein-like substance. The particle-phase BrC was rich in humic-like substance (HULIS).